THE ROLE OF LEADERSHIP SOFT SKILLS IN PROMOTING THE LEARNING ENTREPRENEURSHIP - Sadq, Zana Majed (Journal of process management and new technologies, 2019)
This study is interested in identifying the role of leadership soft skills that its dimensions comprised of (communication skills, initiative skills, training skills, and team building skills) according to the views of the Members of College Councils in a sample of colleges of Salahaddin University, Erbil/ Iraq in promoting learning entrepreneurship that its dimensions comprised of (leadership efficiency, Entrepreneurship intention, and daring behavior) through a field testing study variables that based on the theoretical and methodological frameworks. A survey questionnaire has been designed and distributed to members of the colleges' Councils of a number of colleges of Salahaddin University that numbered 41 respondents in order to verify study hypotheses that have been developed to address the study problem. The most important results that the study reached are there is a positive correlation and an impact of leadership soft skills and learning entrepreneurship collectively and individually. Based on the results, this study presented a set of recommendations such as the necessity to increase the awareness of individuals in organizations about the importance of leadership soft skills, and seek to exploit and embrace untapped opportunities along with creating the accurate climate to work as a team in order to improve the performance and achievement goals.